Protective immunity and delayed type hypersensitivity reaction are uncoupled in experimental Leishmania major infection of CCR6-negative mice - Lechner, Anja; Ritter, Uwe; Varona, Rosa; Marquez, Gabriel; Bogdan, Christian; Körner, Heinrich (Microbes and Infection, 2007)
The chemokine receptor CCR6 is expressed on naïve B cells, dendritic cell and T-cell subpopulations and is involved in cell navigation during organogenesis and recruitment in response to inflammatory stimuli. Gene-deficient C57BL/6 CCR6-/- mice infected with the protozoan parasite Leishmania (L.) major were able to mount a protective immune response and survived the infection. Whereas macrophage production of nitric oxide (NO), the key leishmanicidal effector molecule during the immune response to L. major, did not require CCR6, the migration of CD4+ T cells to the site of infection was reduced in CCR6-/- mice. Furthermore, the induction of a T-cell-dependent delayed-type-hypersensitivity (DTH) reaction was defective in CCR6-/- mice, whereas resistance to re-infection was maintained in the absence of CCR6. We conclude that CCR6 contributes to the recruitment of T cells to the site of infection, but is largely dispensable for the control of L. major parasites during primary or secondary infection. © 2007 Elsevier Masson SAS. All rights reserved.
CRIS-Team Scopus Importer:2024-02-26
Keywords: CC-chemokine receptor 6; Cell migration; Knockout; Lymphocytes; Protozoan parasite